Avaliação da transfusão sanguínea homóloga em ovinos - Sousa, Rejane dos Santos (Universidade Federal Rural do Semi-Árido, 2012)
This study evaluated the clinical, hematological, biochemical and blood gas responses and the oxidative stress in sheep submitted to hiperacute anemia and subsequently underwent to homologous transfusion with whole blood, either fresh, or stored for 15 or 35 days. Eighteen adult Santa Inez crossbred sheep, males and females, were used, weighing on average 52kg. The animals were submitted to a single phlebotomy to remove 40% of blood volume and equally divided into three experimental groups: G0 - animals receiving fresh blood; G15 receiving blood stored for 15 days; and G35 - receiving blood stored for 35 days. The animals were submitted to clinical examination and blood collection 24 h after induction of anemia (T0), 30 minutes after transfusion (T30), six, twelve, twenty-four, forty-eight, seventy-two and ninety-six hours post-transfusion (T6, T12, T24, T48, T72 and T96, respectively), and eight and sixteen days post-transfusion (T8d and T16d, respectively). The blood bags stored for 35 days showed an increase in K, pCO2, pO2, lactate, plasma hemoglobin and decreased plasma pH, sodium and leukocytes. The sheep transfused from all groups had increased GV, red cell count and total hemoglobin in the T30. The animals of the G35 had higher plasma hemoglobin in T12, a significant decrease in blood pH indicating a mild metabolic acidosis on T96. With respect to oxidative stress, was observed a decreased on catalase values of the G35 at T30, T6, T12 and T24, suggesting the occurrence of hemolysis witch was supported by the concomitant increase in the total bilirubin values at the same periods. Animals that received blood stored for 35 days showed higher alteration on hematological, blood gas, biochemical and oxidative stress parameters
Evaluation of homologous blood transfusion in sheep
Keywords: Red blood cells; Oxidative stress; Blood gas analysis; Hemácias; estresse oxidativo; Análises hemogasométrica; CIENCIAS AGRARIAS::MEDICINA VETERINARIA